The Impact of Directors’ and Officers’ Liability Insurance on Corporate Performance: An Empirical Evidence from the Data of Chinese Listed Financial Enterprises - Sun, Zhe (Advances in Social Sciences Research Journal, 2020)
Based on data of the listed banks and insurance companies from 2011-2016, this paper studies the factors affecting directors’ and officers’ liability insurance, the relationship between directors’ and officers’ liability insurance and corporate performance. Empirical research shows that there is a significant positive correlation between the company’s asset-liability ratio, corporate performance and directors’ and officers’ liability insurance. Directors’ and officers’ liability insurance has a significant positive effect on corporate performance of listed banks and insurance companies. The empirical findings of this paper will help to strengthen the understanding of directors’ and officers’ liability insurance in bank and insurance companies and promote the widespread use of directors’ and officers’ liability insurance in the future.